Politeness Strategies in the EFL Classroom: A Pragmatic Analysis of Teacher-Student Interaction - Hieng, Fransiska Orien; Balik, Lusiana Mariyeta; Janggo, Wendelinus Oscar (Linguistics and ELT Journal, 2025)
This study examines the politeness strategies used in English as a Foreign Language (EFL) classrooms, with a focus on teacher-student interactions at St. Gabriel Senior High School, in Maumere. Adopting a descriptive qualitative approach, the study integrates Brown and Levinson’s (1987) politeness theory with Sack, Schegloff, and Jefferson’s (1974) conversation analysis. Data were collected through observations, field notes, audio recordings, transcripts, and questionnaires. To identify politeness strategies, thematic analysis was used, combined with Conversation Analysis to examine interactional features of the data. The analysis revealed that teachers predominantly used positive politeness and bald on record strategies to balance authority, clarity, and rapport. Positive politeness was evident in greetings, praise, empathy, and encouragement, while bald on record strategies were employed for instructional clarity and classroom management. Students frequently demonstrated negative politeness through short, respectful responses that indicated acknowledgement of the classroom hierarchy. CA revealed key interactional features, such as turn taking control, adjacency pairs, repair sequences, and pedagogically functional interruptions. Questionnaire results further confirmed students’ positive perception, which indicating that politeness strategies contributed to comfort, confidence, and active participation. These findings highlight the importance of politeness strategies in ensuring harmonious interactions, promoting engagement, and enhancing the pedagogical atmosphere in EFL settings.